OPPORTUNITIES FOR DEVELOPING LEADERS’ COMMUNICATIVE AND SOCIAL SKILLS IN THE CONTEXT OF DIGITAL TECHNOLOGIES (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article explores the opportunities for developing communicative and social skills among educational leaders within the context of rapidly advancing digital technologies. In today’s educational landscape, school leaders are expected to go beyond traditional management skills and demonstrate the ability to engage effectively in digital communication, foster virtual collaboration, and adapt to hybrid and remote learning environments. The study examines the integration of digital platforms such as Zoom, Google Meet, and Microsoft Teams into school management practices, highlighting both the benefits and the social-psychological challenges that arise. The article also investigates the emergence of new concepts such as digital empathy, digital ethics, virtual leadership, and digital culture — all of which contribute to the evolving model of socially competent leadership. The author analyzes international experiences and presents modern training methodologies aimed at enhancing educational leaders’ communicative capacities in the digital era, while evaluating their applicability to Uzbekistan’s national education system. The findings offer practical guidance for building a socially conscious, digitally fluent leader who can successfully manage educational processes in virtual environments.